A escrita de si do menino e do jovem Serafim Bertaso: cartas entre o colégio interno e a família (1920-1929) - Wendling, Isabel Schapuis (2021)
The following research aimed to understand the childhood and youth days of Serafim Bertaso through his epistolary writings produced when he was attending boarding schools. As source we worked with documents belonging to the private collection of the family and among the seven hundred and twenty-two items, the vast majority were letters written by Serafim and his siblings addressed to their parents while at school age, in addition to school documents, cards and letters written by other family members. Serafim Bertaso, his older sister Elza and his younger brothers Jayme and Ari are the children of the Colonel Ernesto Bertaso, owner of colonization company Bertaso, Maia e Cia, and of the Italian and merchants’ descendant Zenaide Bertaso, birth name Ballista. The letters were written by Serafim from 1926 to 1929 while attending catholic schools, thus the goals consisted in tracing not only the formation and agency of Serafim but also the path which made possible for his family to achieved the social, financial and cultural capital that turned them into a local elite in the city of Chapecó, focusing on how the boy acted within the family environment since he lived many years in elitist and conservative catholic schools where surveillance, strict rules, emulation and rewards were part of the students’ daily life, yet reinforcing ideals of continuous work and overcoming of adversities. The research also considered the age factor in order to analyze and comprehend the agency and subjectivation of Serafim once his epistolary practice was seen as a place of self-reflection and construction of his own subjectivity in face of others. Concerning the family, we noticed a significant effort from the parents in acquiring social networking connections as well as the high investment in the children’s education, sending them to private schools under boarding system. In conclusion, we realized Serafim’s agency occurred in different ways throughout his childhood and adolescent years, moreover we noticed changes in his narrative identities depending on the correspondent he was sending the letters to. At school it was possible to summarize that Serafim developed his agency amidst the rules and how he was allowed to be raised as a young boy belonging to an elite family. In the letters addressed to his parents, Serafim used to report his school development aiming to please the family and show the good use of the family’s wealth in education while developing throughout the years writing techniques that showcase behaviors fitting the school system which he was a part of and he also behaved according to the masculinity practices expected from elite men in Santa Catarina, his home state in Brazil.